Influence of adhesive-composite application modalities on their bonding to tooth structure and resistance of the performed restorations to failure - Khalid M. Abdelaziz; Ahmed A. Saleh (Elsevier, 2018)
Background/purpose: The longevity of bonded composite restorations could be affected by the utilized adhesive-composite application techniques. This in vitro study aimed to evaluate the influence of adhesive-composite application modalities on their bonding values to tooth structure and on the failure resistance of the performed restorations on loading. Materials and methods: Resin composite studs, 2 mm in diameter and 4 mm high, were bonded in 2 groups to flattened enamel and dentin surfaces of 80 extracted premolars using pre-cured (PC) and co-cured (CC) self-etch resin adhesive. Studs in each group were built-up in 4 subgroups using either multiple increments of nano-filled composite (IF, control) or single increment of preheated nano-filled (PH), bulk-fill (BF) and sonic-activated bulk-fill composites (SF). Another 80 premolars with standard class II cavities were also restored using the same adhesive-composite application modalities. All specimens were then stressed on a universal testing machine to assess the composite-tooth shear bond strength and the resistance of the performed restorations to failure. The modes of specimens' failure were also assessed following each test. Results: The PC adhesive provided higher bond strength to dentin (p < 0.05) and comparable bond strength to enamel in comparison to the CC one (p>0.05%). Both PH and BF composites showed lower bond strength to dentin in presence of PC adhesive (p < 0.05). Comparable bond strengths were noticed for PH, BF and SF composites to dentin in presence of CC adhesive (p > 0.05). PH and SF restorations presented the highest resistance to failure (p < 0.05). Conclusion: Both incrementally and bulky-inserted composites offer clinically acceptable bond strength in presence of pre-cured resin adhesive. Both Preheated and sonic-activated composite restorations offer the highest resistance to failure on loading. The preheating procedure renders regular composite material suitable for bulk-fill applications. Keywords: Bond strength, Curing, Failure resistance, Resin adhesive, Resin composite